2013
DOI: 10.1371/journal.pone.0070782
|View full text |Cite|
|
Sign up to set email alerts
|

Structure, Antimicrobial Activities and Mode of Interaction with Membranes of Bovel Phylloseptins from the Painted-Belly Leaf Frog, Phyllomedusa sauvagii

Abstract: Transcriptomic and peptidomic analysis of skin secretions from the Painted-belly leaf frog Phyllomedusa sauvagii led to the identification of 5 novel phylloseptins (PLS-S2 to -S6) and also of phylloseptin-1 (PSN-1, here renamed PLS-S1), the only member of this family previously isolated in this frog. Synthesis and characterization of these phylloseptins revealed differences in their antimicrobial activities. PLS-S1, -S2, and -S4 (79–95% amino acid sequence identity; net charge  = +2) were highly potent and cid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 40 publications
0
34
0
1
Order By: Relevance
“…The homogeneity and identity of the synthetic peptides were assessed by analytical reversed-phase high-performance liquid chromatography (RP-HPLC) on a C18 analytical column (Modulo-cart QS Uptisphere 5 ODB, 5 mm, 250 x 4.6 mm, Interchim, Montluçon, France) and by matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry carried out on a Voyager-DE PRO (Applied Biosystems, Foster City, CA, USA) under the same conditions as described previously (Mass Spectrometry and Proteomics Platform, IBPS, FR 3631 UPMC-CNRS, UPMC, Paris, France) [77]. …”
Section: Methodsmentioning
confidence: 99%
“…The homogeneity and identity of the synthetic peptides were assessed by analytical reversed-phase high-performance liquid chromatography (RP-HPLC) on a C18 analytical column (Modulo-cart QS Uptisphere 5 ODB, 5 mm, 250 x 4.6 mm, Interchim, Montluçon, France) and by matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry carried out on a Voyager-DE PRO (Applied Biosystems, Foster City, CA, USA) under the same conditions as described previously (Mass Spectrometry and Proteomics Platform, IBPS, FR 3631 UPMC-CNRS, UPMC, Paris, France) [77]. …”
Section: Methodsmentioning
confidence: 99%
“…It has also been realized that the cell wall components of bacteria play important roles in insertion and translocation of AMPs toward cytosolic membrane (33)(34)(35). Several studies have demonstrated higher MICs of AMPs for Gram-negative bacteria compared to Gram-positive organisms (36)(37)(38)(39)(40). In particular, LPS of the outer membrane of Gram-negative bacteria has been found to be actively involved in the mode of action of AMPs (5,(41)(42)(43)(44)(45)(46).…”
mentioning
confidence: 99%
“…However, the generated model had a poor statistical quality ( q 2 = 0.142 and r 2 = 0.787, 14 PCs). Analyzing the complete dataset, we tested the exclusion of two peptides, phylloseptin 3 and phylloseptin 5 due to the uncertainty in their respective IC 50 values, which were reported as >60 μ m and not as 60 μ m , as we initially had considered. A new model was obtained showing better results ( q 2 = 0.561 and r 2 = 0.932, 8 PCs).…”
Section: Resultsmentioning
confidence: 99%